Rapid Assessments of Leatherback Small-Scale Fishery Bycatch in Internesting Areas in the Eastern Pacific Ocean - Ortiz-Alvarez, Clara; Pajuelo, Mariela; Grados, Daniel; Abrego, Marino E.; Rebeca Barragán-Rocha, Ana; Barrantes, Mariano; Cotto Sánchez, Alejandro; Fonseca, Luis G.; Gadea Espinal, Velkiss; Mangel, Jeffrey C.; Rguez-Baron, Juan M.; Santidrian-Tomillo, Pilar; et al. (Frontiers in Marine Science, 2020)
The East Pacific (EP) leatherback population is listed by the IUCN Red List of Threatened species as Critically Endangered. Despite conservation efforts, mainly focused around nesting areas, its population has declined by over 90% since the 1980s. The major current threat is fisheries bycatch, but its impact has been primary documented within South American migration and foraging habitats, with scarce information from nesting or interesting areas. To assess the impact of small-scale fisheries on EP leatherbacks inhabiting waters north of the equator we conducted rapid bycatch assessments (surveys) in 5 countries (México, Nicaragua, Costa Rica, Panamá and Colombia), some of which host the main EP leatherback nesting areas. A total of 1,778 surveys were conducted across 79 fishing ports (México = 37, Nicaragua = 6, Costa Rica = 5, Panamá = 17 and Colombia = 14). Leatherback bycatch was reported in all countries, and in 54% of ports surveyed by 7% (n = 125) of fishers interviewed. Surveys enabled identification of areas near nesting beaches (e.g. inter-nesting habitats) where leatherback bycatch was higher and periods during which fisheries interactions events were more frequent. Bycatch events were most frequently reported in gillnets and longlines using “J” hook. Data were scaled up across fishing fleets to estimate that 345 (± 210) individual leatherbacks are caught annually in the ports surveyed. Our study provides a first evaluation of leatherback bycatch by small-scale fisheries in countries of the eastern Pacific Ocean where leatherbacks nest, and it highlights areas close to index nesting beaches where conservation efforts targeting bycatch reduction and bycatch mortality may be focused.